Internet censorship detected in Vietnam (Vietnam) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Vietnam. Data sourced from CensoredPlanet.
Censorship Incident ID: VN-2026-0210. Severity: critical. Confidence: 65%